The Comprehension of English Texts by Native Speakers of English and Japanese, Chinese and Russian Speakers of English as a Lingua Franca: An Empirical Study - Stine Evald Bentsen (Copenhagen Business School (CBS), 2018)
Based on the assumption that language is more than a neutral means of communication, and our mother tongue is strongly anchored in our body, mind and culture, this project investigates the comprehension of English texts by native and non-native speakers of English from England, China, Japan and Russia. This project takes its starting point in Durst-Andersen's understanding of language as a system of signs which highlights the fundamental role of the lexicon of our mother tongue in anchoring words not only in our mind but also in our body through its process of acquisition, establishing at the same time the intrinsic link between language and culture. For this project, I view comprehension as an integrated part of the communication process. This understanding shows how speaker and hearer are able to meet in communication, first through the common voice of grammar, which serves as the end point of the speaker's role in communication and marks the starting point for the hearer's part in communication. This is the physical point of contact. And second, through the process of anchoring, where the hearer backtracks the journey made by the speaker to recreate in her own mind what lied before. This is the mental point of contact. Thus, comprehension is layered and the full understanding of an utterance involves comprehending both layers, i.e. reaching both meeting points. Focusing specifically on the comprehension of the disjunctive particle `or' and the comprehension of directives, I investigate (1) how the same English texts are comprehended by native speakers of English from England and non-native speakers of English from Japan, China and Russian, respectively, (2) what the differences and/or similarities are, and (3) what these differences and/or similarities tell us about comprehension in a foreign language compared to a mother tongue. This was investigated through a qualitative analysis of data collected through the GEBCom Reception Test, designed specifically for this purpose. The test consists of 36 short texts evolving around ten different elements of interest. Following each text is a series of questions with multiplechoice answers designed to elicit the participants' comprehension of the text. The participants were 90 university students from England, Japan, China and Russia. Findings from the comprehension of `or' showed how all native speakers made an inclusive interpretation of the disjunctive particle, i.e. as meaning `both… and', indicating that for native speakers of English this seems to be a grammatical distinction. Though all three groups of non-native speakers shared the inclusive reading, a rather large portion of especially the Chinese and Japanese speakers of English differed from this understanding and comprehended `or' in this text as meaning `either… or'. The findings from the comprehension of directives also showed similarities in comprehension between native speakers and non-native speakers but highlighted many differences as well. The analysis of the native speakers' comprehension showed how the specific communication process of English seemed to influence their comprehension of directives, affecting their overall understanding both in terms of how polite they perceived the text, what intention they ascribed to it and which course of action they would take after having read it. Common for the non-native speakers' comprehension across texts was the fact that even though they seemed to form the same basic understanding, i.e. reach the same physical point of contact as the native speakers, the journey they made from here was different, meaning they ended up forming a different full understanding of the texts, be this in terms of their evaluation of politeness, their interpretation of the intention behind the text or the course of action they would take subsequently. Taken together the findings from this project showed that the process of comprehension in ELF is complex, suggesting that it may not always be possible or even relevant to conceptualise transfer as a direct transfer from mother tongue to foreign language, but rather as a subtle influence with possible profound influence for the overall understanding.
hdl:10398/9651
Keywords: 650